Automatic verification and data processing system of indicator based on grating principle - Lingmei Li; Ruijun Lu; Yiqing Ma; Hongguang Liu (The Journal of Engineering, 2019)
The rapid progress of modern science and technology promotes the continuous development of precision measurement technology and improves the accuracy and efficiency of measuring instruments. In optical precision measurement technology, grating measurement technology has the advantage of high precision and large range. This study introduces the principle, structure and data handling of grating tester for dial indicator gauges. As the grating tester for dial indicator gauges is a kind of high precision measuring standard instrument, the verification basis, verification method and uncertainty analysis are also discussed in depth in this study.